Prevalence and clinical correlates of psychiatric morbidity among caregivers of patients attending a psychiatric hospital in North India - Rather, Yasir Hassan; Dar, Mansoor Ahmad; Bhat, Fazle Roub; Shah, Majid Shafi; Wani, Rayees Ahmad (International Journal of Research in Medical Sciences, 2020)
Background: Consequent to the high prevalence of psychiatric disorders in present day world, their caregivers form an important group in the public health. Research on the physical and psychological well-being of caregivers is being carried worldwide with varied results. Psychological health of these caregivers is usually ignored both by these persons themselves and the health-care providers. The objective of the study was to screen for psychiatric morbidity among caregivers of patients attending a psychiatric hospital in North India, and to study the clinical correlates of the same. Methods: A total of 205 patients and their caregivers were consecutively recruited over a one month period. Sociodemographic and clinical information of patients was obtained either from the hospital records or from the caregiver. Scoring of the patient’s global assessment of functioning (GAF) was done by clinicians. The caregivers were administered a sociodemographic questionnaire, general health questionnaire (GHQ-12) and Zarit Burden interview. The presence of psychiatric morbidity was confirmed by a consultant psychiatrist. Results: Among the caregivers, 32.2% had GHQ scores of 3 and above. Majority of caregivers in this study were females (59.0%) while as majority of the patients were males (61.9%). Factors associated with psychiatric morbidity among caregivers include the high level of subjective burden of care, low level of functioning, and comorbid medical and psychiatric conditions. Conclusions: The study reveals a high level of psychiatric morbidity among the caregivers of patients with mental health problems.